THE IMPACT OF ENGLISH ON GLOBAL MARKETS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
English has become the primary language for international business, trade, and communication. This paper examines how English facilitates the growth of multinational corporations, enhances global trade, and supports financial markets. The study highlights the role of English in connecting businesses across borders and promoting international collaboration in various sectors, such as technology and marketing.